Assessment of Credit Reference Bureaus on the Management of Nonperforming Loans in the Banking Industry in Kenya A Case of Nairobi County - Mutungú, Charles; sang, William; Shisia, Adam; Okibo, Walter Bichanga (My University, 2014)
The purpose of this study was to find out the role of (CRB) in the management of nonperforming loans in Kenya’s banking industry. This study also sought to evaluate the effect of information sharing by Credit Reference Bureaus regulation on nonperforming loans and to establish the extent to which reputation collateral and blacklisting has on management of bad debt in Kenya’s Banking industry. The study sourced data from secondary sources. The data was obtained from financial reports, library, and banks’s records such as in-house magazines, journals, publications as well as website and other resourceful information available for 5 years from 2008 to 2013,the duration when the CRB regulation has been in operation. A regression relationship was generated to show the extent to which each independent variable influenced the dependent variable. A correlation analysis was also performed to find how the variables are related to each other in the model. The research findings showed that the CRB plays a major role in managing nonperforming loans. Reputation collateral and blacklisting do have both positive and negative effect respectively on the management of bad debt in Kenya’s Banking industry. In addition, CRB firms in Kenya should link with other regional CRB firms in other countries as to have information on credit histories of those crossing the borders. The study also revealed that lack of awareness and non-compliance are currently the major challenges of CRB application in Kenya. The study recommends that the CRB be extended to all non-banking sectors that handle credit transactions since this will reveal more credit histories of different borrowers.
Keywords: Credit Reference Bureaus; Non Performing Loans; Credit Histories